The expectations of prospective students regarding the economic returns to higher education: Evidence from Cyprus - Eliophotou-Menon, Maria; Andreou, Sofia N.; Markadjis, Elias (My University, 2020)
The paper investigates the expectations of prospective university students in Cyprus in relation to the returns to higher education. Specifically, we estimate the expected rates of return to a higher degree and compare the estimates of respondents based on the intended field of study and country of study. Moreover, we estimate expected rates of return for students of different socioeconomic backgrounds. The data used for the estimation were collected from 2051 students in their final year of secondary education in Cyprus in January and February of 2013. The findings point to rational expectations on the part of prospective students. Of the four most popular country destinations, the highest rate of return was expected by respondents intending to study in the United Kingdom. As regards field of study, Medicine and related fields were associated with the highest rate of return. Children of higher parental educational and occupational levels expected higher rates of return. In regression analysis, several variables were significantly linked to the expected rate of return. These included the respondent’s socioeconomic status, the field of study, the country of study (students intending to study in Cyprus expected lower rates), student ability, and urban/semi-urban residence. The paper discusses the implications of the findings for educational planning and policy making in higher education.
Keywords: Rates of return to education; Student expectations; Higher education